PEMANFAATAN FILM ANIMASI SEBAGAI MEDIA PEMBELAJARAN ANAK BERBASIS FLASHMX - Supriyadi Sandi (Universitas Bina Sarana Informatika, 2021)
Entertainment-based education can be done by teachers and parents to design learning materials about soft skills in children such as helping children. The usefulness of this animated film, has a function as an entertainment tool and as a learning medium for children so that children do not feel bored and are able to provide freshness because of the entertainment element. Of the many animated films that are shown, not many teach about something that contains the meaning of goodness, for example the attitude of helping each other. After making this film, it shows that this film has an interesting storyline and is worthy to be watched by children aged 2-8 years and contains educational values both morally and religiously and can entertain children. Children always want to help people who are having difficulties, namely by helping everyone so that they can help ease the burden of suffering from others and get a reward from the creator. The making of this animation using Macromedia Flash MX software by adding a mixture of visual effects in each scene to make it more interesting and the picture clearer